(untitled) (Al-Qamar, 2021)
Jihād is an Islamic term which is to be considered in wide range of meanings. However in Islamic etymological background, Jihād is waged against the transgressors, tyrants and those who rebel against an Islamic state. Allāma Iqbāl’s concept of Jihād is more widened and he considers Jihād in the way of Allah as the emblem of establishing freedom, peace and eradicating every type of Muslims’ exploitation. His juxtaposition to the concept of Jihād is not mere poetic, yet philosophical and practical due to that Muslims can acquire complete self -freedom, freedom from sins , freedom from internal and external subjugating forces and it helps Muslims to establish a peaceful society.